2004
DOI: 10.1038/sj.onc.1207768
|View full text |Cite
|
Sign up to set email alerts
|

Inverted signaling hierarchy between RAS and RAC in T-lymphocytes

Abstract: In order to generate coherent biological responses to extracellular stimuli, cells have established synergistic and antagonistic crosstalk between pathways with similar or opposing functions, respectively. Two routes cooperating in the generation of mitogenic and cytoskeletal functions are those induced by Ras and Rho/Rac GTPases. In these signaling interactions, Rho/Rac proteins have been always placed in a downstream position respect to Ras in all cell systems analysed so far. In this report, we describe tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 46 publications
2
48
0
1
Order By: Relevance
“…To study whether a similar regulation occurred in T-cells, we monitored the changes in the subcellular localization of EGFP-tagged α2-and β□-chimaerin upon the treatment of Jurkat cells with anti-CD3 antibodies for 5 min. As positive control, we used an EGFP fused to RasGRP1, a DAGdependent GEF for Ras that has been shown before to translocate to the plasma membrane of lymphocytes upon similar stimulation conditions [52,53]. Unexpectedly, we found that the stimulation of the TCR did not induce any translocation of chimaerin family members to membrane structures (Fig 5A, see first and second rows of panels from top).…”
Section: Chimaerin Proteins Do Not Translocate To the Plasma Membranementioning
confidence: 99%
“…To study whether a similar regulation occurred in T-cells, we monitored the changes in the subcellular localization of EGFP-tagged α2-and β□-chimaerin upon the treatment of Jurkat cells with anti-CD3 antibodies for 5 min. As positive control, we used an EGFP fused to RasGRP1, a DAGdependent GEF for Ras that has been shown before to translocate to the plasma membrane of lymphocytes upon similar stimulation conditions [52,53]. Unexpectedly, we found that the stimulation of the TCR did not induce any translocation of chimaerin family members to membrane structures (Fig 5A, see first and second rows of panels from top).…”
Section: Chimaerin Proteins Do Not Translocate To the Plasma Membranementioning
confidence: 99%
“…It has been reported that T cell receptor engagement by antigen promotes the rapid activation of these GTPases together with an array of other signaling molecules (12,13). Subsequently, Rac proteins transduce signals through intermediate signaling molecules, most notably PKC (14), phosphatidylinositol 3-kinase (PI3K) (5), calcium (15), and PLC␥1 (13).…”
mentioning
confidence: 99%
“…Subsequently, Rac proteins transduce signals through intermediate signaling molecules, most notably PKC (14), phosphatidylinositol 3-kinase (PI3K) (5), calcium (15), and PLC␥1 (13). Importantly, Rac1 controls the translocation of RasGRP1 (a guanine nucleotide exchange factor for Ras) to the actin juxtamembrane structures to facilitate Ras/ERK pathway activation (12). The integration of these signaling events reaches the nucleus via AP-1, nuclear factor of activated T cells, NF-B, and JNK.…”
mentioning
confidence: 99%
“…This molecular structure and its potential to establish intermolecular interactions result in a complex and flexible platform for both recognition and processing information as well as the transduction of signals to the cell cytosol and the nucleus. B lymphocytes may be maintained in a quiescent state and stimulation of BCR leads to potent activation of signalling molecules, such as the small GTPases of the Ras superfamily [2][3][4][5] mediating the activation of intracellular signalling cascades [2][3][4][5][6][7][8][9]. Briefly, BCR stimulates the activity of both the Syk [10,11] and the Src family of protein tyrosine kinases [12] leading to the activation of the B cell signalosome, which includes the adapter protein BLNK (B cell linker-protein), Bruton's tyrosine kinase (BTK) and phospholipase Cc2 (PLCc2) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, BCR stimulates the activity of both the Syk [10,11] and the Src family of protein tyrosine kinases [12] leading to the activation of the B cell signalosome, which includes the adapter protein BLNK (B cell linker-protein), Bruton's tyrosine kinase (BTK) and phospholipase Cc2 (PLCc2) [13,14]. PLCc2 in its active state, hydrolyses the membrane component phosphatidylinositol-4,5-bisphosphate (PIP 2 ), resulting in the second messengers inositol-1,4,5-trisphosphate (IP 3 ) and diacylglycerol (DAG). IP 3 binds to IP 3 receptors in specialized areas of the endoplasmic reticulum triggering Ca 2+ release [15], while DAG remains attached to the inner region of the plasma membrane and serves to recruit and contribute to activating the cytosolic protein kinase C (PKC) [16].…”
Section: Introductionmentioning
confidence: 99%